2008
DOI: 10.1021/bi801040b
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsically Disordered RNR Inhibitor Sml1 Is a Dynamic Dimer

Abstract: Sml1 is a small ribonucleotide reductase (RNR) regulatory protein in Saccharomyces cerevisiae that binds to and inhibits RNR activation. NMR studies of 15N-labeled Sml1 (104 residues), as well as of a truncated variant (residues 50-104), have allowed characterization of their molecular properties. Sml1 belongs to the class of intrinsically disordered proteins with high degree of dynamics and very little stable structures. Earlier suggestions for a dimeric structure of Sml1 were confirmed and from translation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 42 publications
2
54
0
1
Order By: Relevance
“…The data presented here suggest that αSyn is like many other proteins whose structure depends on subunit concentration and environmental factors (26). In vitro, and probably in vivo, an equilibrium exists between unfolded monomer, compact oligomer, and (perhaps) amyloid-forming species.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The data presented here suggest that αSyn is like many other proteins whose structure depends on subunit concentration and environmental factors (26). In vitro, and probably in vivo, an equilibrium exists between unfolded monomer, compact oligomer, and (perhaps) amyloid-forming species.…”
Section: Discussionmentioning
confidence: 67%
“…The formation of a secondary structure in the absence of lipids or micelles is likely in response to intersubunit hydrophobic interactions that drive oligomer formation, as has been observed for other intrinsically disordered proteins (26). Indeed, 1 H, 15 N-HSQC spectra of dilute (50 μM) αSyn construct show clear correlations only for the C-terminal residues, suggesting an increase in dynamic broadening due to an equilibrium between more compact and extended forms of the protein at low concentrations.…”
Section: Discussionmentioning
confidence: 71%
“…55,56 Therefore, a large number of theoretical 55,57 and experimental studies 14,18,[58][59][60][61] of IDPs has focused on identifying elements of partially formed secondary structure, particularly a-helices. In experimental studies trying to identify partially formed helices, it is desirable to work under conditions where the helical elements have the highest population.…”
Section: Discussionmentioning
confidence: 99%
“…12 Despite the structural decoupling between distant regions of IDPs, even highly disordered proteins have been found not to be elongated but still to form specific tertiary and even quaternary interactions. [13][14][15] The heterogeneous nature of IDPs means that their structure is best described by an ensemble of structures containing both long range and local interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that disrupting mutations in the TRP domain might have a high influence on the activation energy of channel gating, suggesting that TRP domain interactions between monomers are critical for channel gating [16]. Despite the intrinsically disordered structure of some proteins, they are still able of forming oligomers, such as the dynamic dimer formed by the small disordered ribonuclease reductase Sm11 [44], HIV-1 Vif [45], the disordered inhibitory domains of the coiled-coil dimeric kinases [46], the termini of coiled-coil dimeric proteins involved in signaling pathways [47], or the cytoplasmic domain of the f-chain of the T-cell receptor. This latter domain has been demonstrated to form homodimers without a disorder-order transition [48].…”
Section: Discussionmentioning
confidence: 99%